GCSE German : The Revision Guide - Edited by Parsons, Richard (Kirkby-in-Furness Coordination Group Publication Ltd, 2000)
Containing important vocabulary and phrases needed for the key topics students need to know, this guide also tackles the mysteries of German grammar in simple terms with a German-English dictionary section. This is a useful resource for GCSE.
Include Color Illustration, Dictionary and Index
Keywords: German language